Enhanced Conversion in the Direct Synthesis of Diethyl Carbonate from Ethanol and CO 2 by Process Intensification (2023)
To overcome the low equilibrium conversion in the direct synthesis of diethyl carbonate from ethanol and CO 2 under moderate reaction conditions, the reaction was conducted in a membrane reactor packed with pelletized Cu-Ni:3-1 supported on activated carbon. A SiO 2 /?-Al 2 O 3 commercial membrane and zeolite A membranes synthesized on commercial Al 2 O 3 supports were evaluated in the membrane reactor. Although characterization of the membranes by X-ray diffraction confirmed the presence of a zeolite A layer on the supports, gas permeation and permselectivity tests of ethanol and water evidenced some defects of the synthesized membranes. An increase in conversion with respect to a conventional packed-bed reactor was observed in the membrane reactors prepared on Al 2 O 3 , but equilibrium conversion was not attained. However, with the commercial membrane, the ethanol conversion was higher than the equilibrium conversion. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim